Variability of serum markers of erythropoiesis during 6 days of racing in highly trained cyclists - Voss, S. C.; Alsayrafi, M.; Bourdon, P. C.; Klodt, F.; Nonis, D.; Hopkins, W. G.; Schumacher, Y. O. (International Journal of Sports Medicine, 2014)
The athlete biological passport for the fight against doping is currently based on longitudinal monitoring for abnormal changes in cellular blood parameters. Serum parameters related to altered erythropoiesis could be considered for inclusion in the passport. The aim of this study was to quantify the changes in such parameters in athletes during a period of intense exercise. 12 highly trained cyclists tapered for 3 days before 6 days of simulated intense stage racing. Morning and afternoon blood samples were taken on most days and analysed for total protein, albumin, soluble transferrin receptor and ferritin concentrations. Plasma volume was determined via total haemoglobin mass measured by carbon-monoxide rebreathing. Percent changes in means from baseline and percent standard errors of measurement (analytical error plus intra-athlete variation) on each measurement occasion were estimated with mixed linear modelling of log-transformed measures. Means of all variables changed substantially in the days following the onset of racing, ranging from -13% (haemoglobin concentration) to +27% (ferritin). After the second day, errors of measurement were generally twice those at baseline. Plasma variables were affected by heavy exercise, either because of changes in plasma volume (total protein, albumin, haemoglobin), acute phase/inflammatory reactions (ferritin) or both (soluble transferrin receptor). These effects need to be taken into consideration when integrating a plasma parameter into the biological passport model for athletes.